DIFFERENCES KNOWLEDGE, ATTITUDE, AND MOTIVATION PARTICIPANTS BPJS HEALTH MOTHER POST BID TO CHOOSE CONTRACEPTIVE MKJP TOOLS IN BANYUMAS DISTRICT - Ulfah Musdalifah; Anita Widiastuti; Sumiyati Sumiyati (JURNAL KEBIDANAN, 2017)
Maternal has greatest mortality of reproductive age (20-35 years), this age throughs the phases of the life cycle so it needs a continuum carelife cycle. PUS data in Puskesmas 1 Baturraden of Banyumas Regency 5079, while those who participated in BPJS Health 4079.Some factors such as knowledge, attitude, and motivation affect the choice of contraception method MKJP Based on the background, researchers are interested to take the title ".Differences of knowledge, attitude, and motivation Participants BPJS Health PBI In Post-Copy Mother To Select Contraception MKJP in Banyumas Regency     The purpose of this study is to analyze the differences of knowledge, attitude, and motivation between Participants BPJS Maternal Health Post Copy To Select Contraception MKJP. This research is useful for researchers, Puskesmas, BPJS Health, and Mother Post partum as input to immediately join BPJS Health so that it can monitor health throughout health cycle especially at reproductive age.     The type of research is comparative observational analytics with cross sectional design. The study population were all post-partum mothers in Puskesmas II Baturraden of Banyumas Regency with the formula of Lemesow obtained sample of 96 post-saline mothers. Sampling technique is Proporsive Sampling. Independent variables include knowledge, attitude, and motivation while the Dependent variable is MKJP's contraceptive tool. Data analysis are univariate, and bivariate by Chi-Square.     Results of research on knowledge obtained P = 1.82 while P 0.05, attitudes obtained P = 0.403 while P 0.05, the motivation obtained P = 1.82 while P 0.05, all showed no differenceConclusion there is no difference of knowledge, attitudes, and motivation of BPJS participants Maternal post-salt mothers to choose MKJP contraceptives. Sugges-tions are directed to health workers to be more active in providing information, involving professional organizations and non-governmental organizations assisting the MKJP program.